Diagnosis of atrial thrombi by ultrasound. Issue 7 (July 1982) - Donaldson, R M; Ballester, M; Olsen, E
Abstract : Left atrial thrombi were shown by two-dimensional echocardiography in three patients with mitral valve disease and neurological symptoms. In two patients the atrial thrombi had probably been the source of a previous cerebrovascular embolus. In the third, two-dimensional echocardiography detected the development of a recent ball-valve thrombus in the left atrial cavity, which caused intermittent obstruction and syncope. Echocardiographic findings were correlated with anatomical and histological data in all three patients. The spatial orientation provided by the multiple imaging planes of two-dimensional echocardiography permitted correct estimates of the size and position of the thrombus, and this mode was superior to the standard M-mode technique for non-invasive imaging of thrombus. Despite limitations of technique and resolution, the information provided by ultrasound can be extremely helpful in the management of patients. Ultrasonic screening (particularly the two-dimensional mode) is to be recommended in patients with neurological symptoms and clinical evidence of cardiac disease or arrhythmia.